EVALUASI IMPLEMENTASI PENDIDIKAN NILAI DALAM PEMBELAJARAN PENJAS - FAJAR ARI WIDIYATMOKO; MAFTUKIN HUDAH (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2017)
This study was aimed to obtain empirical data on the implementation of value education in physical education learning both in the Learning Implementation Plan (RPP) and in the process of learning practiced in the field. Data were collected in two steps: first, the data will be collected on the Learning Plan (RPP) which has been prepared by the teacher of Physical Education to find the presence or absence of content value education in which the data analysis performed on 100 sample RPP shows that there is 100% . The second step was to deepen the understanding of teachers about the value of education taught to learners and observation of the implementation of value education in the learning process. Of the 100% RPP that contained educational or character values, however only 65% or 13 out of 20 teachers were taken at random, applying the educational value in the learning, 35% did not apply. Of the 65% of teachers applying only 5 teachersÂ  applied the educational values from the opening, main activities and closing activities, 8 teachers only applied from the opening and closing only in the form of prayer and advice to the students.